Functional and structural proteomics of glycoproteins - Owens, Raymond; Owens, Raymond J.; Nettleship, Joanne E. (SpringerLink, 2011)
It has been predicted that nearly half of all human proteins are glycosylated indicating the significance of glycoproteins in human health and disease. For example, the glycans attached to proteins have emerged as important biomarkers in the diagnosis of diseases such as cancers and play a significant role in how pathogenic viruses gain entry into human cells. The study of glycoproteins has now become a truly proteomic science. In the last few years, technology developments including in silico methods, high throughput separation and detection techniques have accelerated the characterization of.